The Role of Economic Reforms in increasing Tax revenues in Iraq: Applied Research (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to explain the role of economic reforms in increasing public revenues in Iraq to the General Authority for Taxes because of its importance and direct impact on the economic and social reality and its significant impact on tax revenues. Therefore, today it has become the greatest role for governments, institutions and international organizations to understand the basic concepts of economic reforms, develop a working mechanism for tax reform, and implement reform programs through implementing tax reform programs, to achieve high and sustainable economic growth rates. To achieve high and sustainable economic growth rates, attract external capital and encourage foreign investment, the role of the state and privatization programs, develop education, develop human capabilities, and invest in the oil sector. One of the most important findings of the research Investment spending is significantly lower than current spending, and this affects the state in developing the industrial and agricultural sectors, since the Iraqi economy depends largely on oil revenues to finance the state’s general revenues, as the average oil revenues during the study period reached (87.39%) In contrast to the decrease in the percentage of non-oil revenue contribution to (12.61%), which is a low percentage, and it is clear that there is a defect in directing public spending to consumption instead of investment, Neglecting tax revenues from public revenues, and the most important recommendations for achieving economic development come through diversifying the Iraqi economy, working to develop industry and agriculture, reducing dependence on oil revenues to finance public revenues, and directing financial surpluses towards areas of investment in infrastructure or directing them towards sovereign wealth funds to ensure economic stability.